Inhabitants : indigenous perspectives on restoring our world [videorecording (DVD)] - Boutsikaris, Costa (Good Docs, 2021)
Follows five Native American communities as they restore their traditional land management practices in the face of a changing climate. For millennia Native Americans successfully stewarded and shaped their landscapes, but centuries of colonization have disrupted their ability to maintain these processes. From deserts, coastlines, forests, mountains, and prairies, Native communities across the US are restoring their ancient relationships with the land. The five stories include sustaining traditions of Hopi dryland farming in Arizona; restoring buffalo to the Blackfeet reservation in Montana; maintaining sustainable forestry on the Menominee reservation in Wisconsin; reviving native food forests in Hawaii; and returning prescribed fire to the landscape by the Karuk Tribe of California. As the climate crisis escalates, these time-tested practices of North America's original inhabitants are becoming increasingly essential in a rapidly changing world.